Examining the determination of flood victim's knowledge sharing behavior: From the perspectives of social cognitive theory - Mohamad Zani, N.; Hashim, Kamarul Faizal; Ahmad, Mazida; Ahmad, M. N. (2014)
During the occurrence of disaster, knowledge sharing plays as important role.Through effective knowledge sharing, it can help victims save lives; received immediate relief and support; and minimize the disaster effect.But lack of works has been done to examine the determinants of knowledge sharing within disaster management context. Therefore, this study aims to provide a better understanding of knowledge sharing during the occurrence of disaster.In order to examine the determinant of individual's knowledge sharing behavior during the occurrence of disaster, the researcher will use social cognitive theory (SCT) to conceptualize a theoretical model for this study.This study holds self-efficacy, reciprocity, social support and social recognition as an influence individual in sharing knowledge during the occurrence of disaster.The methodology begins with constructing a questionnaire to investigate the theoretical model.The respondents are victims that have had experience in sharing knowledge during the flood.This study was used a Structural Equation Modeling(SEM)to test causal relationships between constructs.Hopefully, by proposed theoretical model through this research can provide additional insight on what influence knowledge sharing behavior within disaster management context.